2018
DOI: 10.1039/c8ra06674d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the distribution and mixing of cellulose nanocrystals in thermoplastic composites using Raman chemical imaging

Abstract: Raman chemical imaging is presented to both quantify the dispersion and the degree of mixing in a cellulose nanocrystal composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
8
2
Order By: Relevance
“…Selected References Fracture of the cellulose-based reinforcement Summerscales et al 2010;Alavi et al 2013;Fonseca-Valero et al 2015;He et al 2016 Debonding between the matrix & reinforcement Alavi et al 2013;He et al 2016;Mu et al 2018;Simao et al 2019 Debonding within agglomerates of cellulosebased reinforcements Ismail & Shafiq 2016;Lewandowska et al 2018;DiLoreto et al 2019 Large increases in strength when using compatibilizing agents George et al 2001;Fu et al 2008;Farsi 2012;Alavi et al 2013;Durmus et al 2019 The quality of bonding between a cellulosic surface and a plastic matrix material tends to be of critical importance. Gaugler et al (2019) recently showed that such bonds can be evaluated quickly and precisely by preparing sandwich-type composites.…”
Section: Type Of Mechanistic Evidencementioning
confidence: 99%
“…Selected References Fracture of the cellulose-based reinforcement Summerscales et al 2010;Alavi et al 2013;Fonseca-Valero et al 2015;He et al 2016 Debonding between the matrix & reinforcement Alavi et al 2013;He et al 2016;Mu et al 2018;Simao et al 2019 Debonding within agglomerates of cellulosebased reinforcements Ismail & Shafiq 2016;Lewandowska et al 2018;DiLoreto et al 2019 Large increases in strength when using compatibilizing agents George et al 2001;Fu et al 2008;Farsi 2012;Alavi et al 2013;Durmus et al 2019 The quality of bonding between a cellulosic surface and a plastic matrix material tends to be of critical importance. Gaugler et al (2019) recently showed that such bonds can be evaluated quickly and precisely by preparing sandwich-type composites.…”
Section: Type Of Mechanistic Evidencementioning
confidence: 99%
“…Confocal Raman microscopy is being increasing applied to study composites of CNs [31,32,33,34,35,36]. Typically, the nanocomposites consist of thermoplastics and CNs.…”
Section: Cellulose Materialsmentioning
confidence: 99%
“…Such analysis showed that CNCs were aggregated to varying degrees in the composites and remained poorly dispersed in the polypropylene matrix. A recent study was performed to evaluate quantitatively distribution of CNCs in high-density polyethylene (HDPE) composites [33]. The Composites were prepared using maleic anhydride modified polyethylene (MAPE) and poly(ethylene oxide) (PEO) as a compatibilizer.…”
Section: Cellulose Materialsmentioning
confidence: 99%
“…The matrix spectrum clearly consists of both the polymer and CNC spectra, and can be discerned at a glance. The presence of this dispersed material is more difficult to establish using the other techniques—Raman microscopy requires deconvolution of the two spectra from one another and a weak CNC signal may not be detected (Agarwal et al, 2012; Lewandowska & Eichhorn, 2016; Lewandowska et al, 2018). However, background noise from the polymer, which risks the generation of false-positive results, makes it difficult to confidently identify aggregates that are less than 11 µ m 2 in area, equivalent to ten pixels, with the objective used.…”
Section: Resultsmentioning
confidence: 99%
“…Although Nigmatullin et al had success in distinguishing cellulose nanocrystals, CNCs, from starch using adhesion mapping (Nigmatullin et al, 2018), the observable volume is limited to around 150 × 150 × 15 µ m 3 . Chemical mapping using confocal Raman spectroscopy (CRS) is a well-established technique (Stewart et al, 2012) that has been successfully applied by Agarwal et al to distinguish between CNCs and polypropylene, mapping the density of CNCs in areas up to 100 × 100 µ m 2 (Agarwal et al, 2012) and Lewandowska et al have mapped areas containing CNCs and polyethylene up to 200 × 200 µ m 2 (Lewandowska & Eichhorn, 2016; Lewandowska et al, 2018). However, the observable area is still limited, and the process is time consuming, often requiring more than half a day to acquire and analyze each image.…”
Section: Introductionmentioning
confidence: 99%